# Find the values of k for which the quadratic equation $(3k + 1)x^2 + 2(k + 1)x + 1 = 0$ has equal roots. Also, find the roots.

Given:

Given quadratic equation is $(3k + 1)x^2 + 2(k + 1)x + 1 = 0$.

To do:

We have to find the value of k for which the given quadratic equation has equal roots.

Solution:

$(3k + 1)x^2 + 2(k + 1)x + 1 = 0$

Comparing the given quadratic equation with the standard form of the quadratic equation $ax^2+bx+c=0$, we get,

$a=3k+1, b=2(k+1)$ and $c=1$.

The discriminant of the standard form of the quadratic equation $ax^2+bx+c=0$ is $D=b^2-4ac$.

$D=[2(k+1)]^2-4(3k+1)(1)$

$D=4(k+1)^2-4(3k+1)$

$D=4(k^2+2k+1)-12k-4$

$D=4k^2+8k+4-12k-4$

$D=4k^2-4k$

The given quadratic equation has equal roots if $D=0$.

Therefore,

$4k^2-4k=0$

$4k(k-1)=0$

$4k=0$ or $k-1=0$

$k=0$ or $k=1$

The values of k are $0$ and $1$.

For $k = 0$,

$(3k + 1)x^2 + 2(k + 1)x + 1 = 0$

$(3(0) + 1)x^2 + 2(0 + 1)x + 1 = 0$

$x^2 + 2x + 1 = 0$

$(x + 1)^2 = 0$

$x+1=0$

$x=-1$

Therefore, for $k=0$ the roots of the given quadratic equation are $1$ and $1$.

For $k = 1$,

$(3k + 1)x^2 + 2(k + 1)x + 1 = 0$

$(3(1) + 1)x^2 + 2(1 + 1)x + 1 = 0$

$4x^2 + 4x + 1 = 0$

$(2x + 1)^2 = 0$

$2x+1=0$

$2x=-1$

$x=\frac{-1}{2}$

Therefore, for $k=1$ the roots of the given quadratic equation are $\frac{-1}{2}$ and $\frac{-1}{2}$.

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

56 Views

##### Kickstart Your Career

Get certified by completing the course

Advertisements